Armstrong's Axioms

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 4

Armstrong’s Axioms

The term Armstrong axioms refer to the sound and complete set of inference
rules or axioms, introduced by William W. Armstrong, that is used to test the
logical implication of functional dependencies. If F is a set of functional
dependencies then the closure of F, denoted as  , is the set of all functional
dependencies logically implied by F. Armstrong’s Axioms are a set of rules, that
when applied repeatedly, generates a closure of functional dependencies. 

Seco
ndary Rules –

These rules can be derived from the above axioms. 


Why armstrong axioms refer to the Sound and Complete ? 
By sound, we mean that given a set of functional dependencies F specified on a
relation schema R, any dependency that we can infer from F by using the
primary rules of Armstrong axioms holds in every relation state r of R that
satisfies the dependencies in F. 
By complete, we mean that using primary rules of Armstrong axioms repeatedly
to infer dependencies until no more dependencies can be inferred results in the
complete set of all possible dependencies that can be inferred from F. 

Introduction to Axioms Rules

 Armstrong's Axioms is a set of rules.


 It provides a simple technique for reasoning about functional
dependencies.
 It was developed by William W. Armstrong in 1974.
 It is used to infer all the functional dependencies on a relational
database.

Various Axioms Rules


A. Primary Rules

Rule 1 Reflexivity
    If A is a set of attributes and B is a subset of A, then A holds B. { A → B }

Rule 2 Augmentation
    If A hold B and C is a set of attributes, then AC holds BC. {AC → BC}
    It means that attribute in dependencies does not change the basic dependencies.

Rule 3 Transitivity
    If A holds B and B holds C, then A holds C.
    If {A → B} and {B → C}, then {A → C}
    A holds B {A → B} means that A functionally determines B.
B. Secondary Rules

Rule 1 Union
    If A holds B and A holds C, then A holds BC.
    If{A → B} and {A → C}, then {A → BC}

Rule 2 Decomposition
    If A holds BC and A holds B, then A holds C.
    If{A → BC} and {A → B}, then {A → C}

Rule 3 Pseudo Transitivity


    If A holds B and BC holds D, then AC holds D.
    If{A → B} and {BC → D}, then {AC → D}

Sometimes Functional Dependency Sets are not able to reduce if the set
has following properties,

1. The Right-hand side set of functional dependency holds only one attribute.
2. The Left-hand side set of functional dependency cannot be reduced, it
changes the entire content of the set.
3. Reducing any functional dependency may change the content of the set.

A set of functional dependencies with the above three properties are also called
as Canonical or Minimal.

Trivial Functional Dependency

Trivial If A holds B {A → B}, where A is a subset of B, then it is called a Trivial


Functional Dependency. Trivial always holds Functional Dependency.

Non-Trivial If A holds B {A → B}, where B is not a subset A, then it is called as a Non-


Trivial Functional Dependency.

Completely Non- If A holds B {A → B}, where A intersect Y = Φ, it is called as a Completely


Trivial Non-Trivial Functional Dependency.

Example:
Consider relation E = (P, Q, R, S, T, U) having set of Functional Dependencies
(FD).
P → Q             P → R
QR → S          Q → T
QR → U          PR → U

Calculate some members of Axioms are as follows,

1. P → T                       
2. PR → S
3. QR → SU      
4. PR → SU

Solution:

1. P → T
In the above FD set, P → Q and Q → T
So, Using Transitive Rule: If {A → B} and {B → C}, then {A → C}
∴ If P → Q and Q → T, then P → T.
P→T

2. PR → S
In the above FD set, P → Q
As, QR → S
So, Using Pseudo Transitivity Rule: If{A → B} and {BC → D}, then {AC
→ D}
∴ If P → Q and QR → S, then PR → S.
PR → S

3. QR → SU
In above FD set, QR → S and QR → U
So, Using Union Rule: If{A → B} and {A → C}, then {A → BC}
∴ If QR → S and QR → U, then QR → SU.
QR → SU

4. PR → SU
So, Using Pseudo Transitivity Rule: If{A → B} and {BC → D}, then {AC
→ D}
∴ If PR → S and PR → U, then PR → SU.
PR → SU

You might also like